Phylogeny, speciation, and distribution of the Japanese dwarf bamboos of genus Sasa and allies. Issue 1 (16th July 2014) - Kobayashi, Mikio
Abstract: Development of the concept of the subfamily Bambusoideae during the past three decades is briefly reviewed. Phylogeny, putative hybrid taxa, a new, simplified key to explicit identification, and the revision of the distribution range among the Japanese dwarf bamboos of genus Sasa and its close allies are discussed. Based on analyses of the random amplified polymorphic DNA and morphological data and of FLOWERING LOCUS T (FT) homologs, parsimonious trees resolved that genus Sasa sec. Macrochlamys were the most basal and sect. Monilicladae were the next most basal, followed by the terminal sister clades of sects. Sasa and Crassinodi . Abstract : Development of the concept of the subfamily Bambusoideae during the last three decades is briefly reviewed. Phylogeny, putative hybrid taxa, a new, simplified key to explicit identification, and the revision of the distribution range among the Japanese dwarf bamboos of genus Sasa and its close allies are discussed.